Copyright in the blockchain era: Promises and challenges. Issue 3 (June 2018) - Savelyev, Alexander
Abstract: The paper focuses on various legal-related aspects of the application of blockchain technologies in the copyright sphere. Specifically, it outlines the existing challenges for distribution of copyrighted works in the digital environment, how they can be solved with blockchain, and what associated issues need to be addressed in this regard. It is argued that blockchain can introduce long-awaited transparency in matters of copyright ownership chain; substantially mitigate risks of online piracy by enabling control over digital copy and creating a civilized market for "used" digital content. It also allows to combine the simplicity of application of creative commons/open source type of licenses with revenue streams, and thus facilitate fair compensation of authors by means of cryptocurrency payments and Smart contracts. However, these benefits do not come without a price: many new issues will need to be resolved to enable the potential of blockchain technologies. Among them are: where to store copyrighted content (on blockchain or "off-chain") and the associated need to adjust the legal status of online intermediaries; how to find a right balance between immutable nature of blockchain records and the necessity to adjust them due to the very nature of copyright law, which assigns ownership based on a set of informal facts, not visible to the public. Blockchain as a kind of time stamping service cannot itself ensure the trustworthiness of facts, which originate "off-chain". More work needs to be done on the legal side: special provisions aimed at facilitating user's trust in blockchain records and their good faith usage of copyrighted works based on them need to be introduced and transactions with cryptocurrencies have to be legalized as well as the status of Smart contracts and their legal consequences. Finally, the economics of blockchain copyright management systems need to be carefully considered in order to ensure that they will have necessary network effects. If those issues are resolved in a satisfactory way, blockchain has the potential to rewrite how the copyright industry functions and digital content is distributed.